Advancing professional nursing practice at the bedside: Five nurses' stories. Issue 3 (March 2023) - Stricklin, Mary Helen; Ashby, Natalie; Merrill, Katreena
Abstract : With staffing shortages, an aging workforce, and pandemic pressures, professional nursing advancement programs may help rejuvenate nurses.